The difference of oropharyngeal microbiome during acute respiratory viral infections in infants and children - Zeni Wu; Mingyue Jiang; Mengmeng Jia; Jian Sang; Qing Wang; Yunshao Xu; Li Qi; Weizhong Yang; Luzhao Feng (Communications Biology)
Abstract Acute respiratory infections (ARI) with multiple types of viruses are common in infants and children. This study was conducted to assess the difference of oropharyngeal microbiome during acute respiratory viral infection using whole-genome shotgun metagenomic sequencing. The overall taxonomic alpha diversity did not differ by the types of infected virus. The beta diversity differed by disease severity, disease-related symptoms, and types of infected virus. Nine species had significantly higher abundance in outpatients than in inpatients, with five of them in the genus Achromobacter. Three microbial community types were identified. The prevalence of community type (CT) 1 was higher among patients with influenza virus, enterovirus, and human adenvirus; CT2 was higher among patients with human metapneumovirus; and CT3 was higher among patients with respiratory syncytial virus and human adenvirus infections. Our results suggest that the oropharyngeal microbiome is associated with ARI disease severity, disease-related symptoms, and the types of infected virus.